Pharmacokinetic/Pharmacodynamic Analysis of Continuous-Infusion Fosfomycin in Combination with Extended-Infusion Cefiderocol or Continuous-Infusion Ceftazidime-Avibactam in a Case Series of Difficult-to-Treat Resistant Pseudomonas aeruginosa Bloodstream Infections and/or Hospital-Acquired Pneumonia - Milo Gatti; Maddalena Giannella; Matteo Rinaldi; Paolo Gaibani; Pierluigi Viale; Federico Pea (MDPI AG, 2022)
Objectives: To perform a pharmacokinetic/pharmacodynamic (PK/PD) analysis of continuous-infusion (CI) fosfomycin combined with extended-infusion (EI) cefiderocol or CI ceftazidime-avibactam in a case series of severe difficult-to-treat Pseudomonas aeruginosa (DTR-PA) infections. Methods: A single-center retrospective study of patients who were treated with CI fosfomycin plus EI cefiderocol or CI ceftazidime-avibactam for severe DTR-PA infections and who underwent therapeutic drug monitoring (TDM), from 1 September 2021 to 30 June 2022 was performed. Concentrations were measured at steady-state (Css) for CI fosfomycin and ceftazidime-avibactam and at trough (Cmin) for EI cefiderocol. Joint PK/PD targets of combination therapy were analyzed (thresholds: area-under-the curve to minimum inhibitory concentration (AUC/MIC) ratio > 40.8 for fosfomycin; ceftazidime Css/MIC ratio ≥ 4 coupled with avibactam Css > 4 mg/L for ceftazidime-avibactam; Cmin/MIC ratio ≥ 4 for cefiderocol). Joint PK/PD targets of the combination therapy were analyzed and defined as optimal when both were achieved, quasi-optimal if only one of the two was achieved, and suboptimal if none of the two was achieved). The relationship between joint PK/PD target attainment and microbiological response was assessed. Results: Six patients (three pneumonia, two BSI + pneumonia, and one BSI) were included. The joint PK/PD targets were optimal in four cases and quasi-optimal in the other two. Microbiological eradication (ME) occurred in 4/4 of patients with optimal joint PK/PD targets and in one of the two patients with quasi-optimal joint PK/PD targets. Conclusions: Attaining optimal joint PK/PD targets with a combo-therapy of CI fosfomycin plus EI cefiderocol or CI ceftazidime-avibactam could represent an effective strategy for granting favorable microbiological outcomes in patients with DTR-PA pneumonia and/or BSI.